Pemberdayaan Kelompok Tani Teman Abadi Tentang Usaha Tani Berbasis Zero-Waste-Agriculture di Kelurahan Mudung Laut - Diah Listyarini; Heri Junedi; Endriani Endriani; Sunarti Sunarti (I-Com: Indonesian Community Journal, 2025)
Horticultural farming in Mudung Laut Village, Pelayangan Subdistrict, is the main livelihood of farmer groups in the area. Farming is carried out using conventional methods, and there is no proper waste management system in place, which has the potential to pollute the environment in the future. The objective of this PPM activity is to empower farming groups in zero-waste agriculture-based farming practices. The PPM activities include: 1) socialization of zero-waste agriculture-based farming practices, composting, biochar, and briquette production; 2) demonstrations and guidance on composting, biochar, and briquette production; 3) application of biochar and compost to farmers' fields; 4) evaluation of the activities. The results of this activity indicate that the knowledge and skills of farmers, particularly those in the Teman Abadi farming group, have increased through the provision of theory and practical experience in zero-waste agriculture, with the hope that farmers can utilize their agricultural waste to enhance the productivity of their farming operations.